2019
DOI: 10.29333/iejme/5768
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes, Study Habits, and Academic Performance of Junior High School Students in Mathematics

Abstract: Mathematics as a discipline is considered as one of the most difficult subjects among Filipino learners. This study was conducted in a public national high school in the Mandaue City Division, Cebu, Philippines. The respondents were the 177 Grade 9 students enrolled in mathematics. These respondents were selected using probability random sampling. They were asked to answer a standardized survey questionnaire to assess their attitudes and study habits. The tool is consists of three parts. Part 1 gathers the soc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
36
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 18 publications
(21 reference statements)
4
36
1
1
Order By: Relevance
“…This positive attitude creates a positive emotion in students towards mathematics subject, eventually influence their willingness to put effort in any mathematical tasks and perform their level best in mathematics quizzes, tests, or examinations. This correlation is consistent with numerous studies such as Andamon and Tan (2018); Capinding (2021); Capuno et al (2019) that strongly emphasized on positive attitude will increase motivation in students and influence their willingness towards the subject. Students become more confident in dealing with any mathematical tasks or solving any mathematics problems.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This positive attitude creates a positive emotion in students towards mathematics subject, eventually influence their willingness to put effort in any mathematical tasks and perform their level best in mathematics quizzes, tests, or examinations. This correlation is consistent with numerous studies such as Andamon and Tan (2018); Capinding (2021); Capuno et al (2019) that strongly emphasized on positive attitude will increase motivation in students and influence their willingness towards the subject. Students become more confident in dealing with any mathematical tasks or solving any mathematics problems.…”
Section: Discussionsupporting
confidence: 92%
“…Kiss (2018) stated that the cognitive component refers to an individual's belief or knowledge about mathematics, the affective component involves feelings about mathematics and the behavior component refers to influence of attitude on how people react. Capuno et al (2019) added that attitudes can be changed as it develops through experience, it is not through inheritance. This is aligned with Syyeda (2016) that mentioned about attitudes can be changed and developed over time.…”
Section: Attitude Towards Mathematicsmentioning
confidence: 99%
“…Several studies have demonstrated a positive correlation between student attitudes towards mathematics and performance in mathematics (Capuno et al, 2019;Elliot et al, 2001;García et al, 2016;Geesa et al, 2019;Guy et al, 2015;Lipnevich et al, 2016). There is a correlation between attitudes towards mathematics and mathematical performance (Ajisuksmo & Saputri, 2017;Frenzel et al, 2007;Opstad, 2018).…”
Section: Gender Performance and Attitudes Towards Mathematicsmentioning
confidence: 99%
“…On the contrary, the increased number of 29.7% within the "Good" level in the posttest from its zero percent (0%) initial rating during the pretest is fundamentally traced from the students' studying the lesson ahead of time since the same was already given to them earlier as assignment. This condition is support by a specific research which accounted that with the kind of study habits that the student have, it can be seen as one of the reasons for their satisfactory performance in mathematics (Capuno et al, 2019). Hence, even if there was only one kind of pyramid that was exhibited, they already knew then that a pyramid could not only have a square or triangle as its base.…”
Section: Results/ Findings and Discussionmentioning
confidence: 58%